Enhancing undergraduate midwifery: using drug and alcohol baby simulators in education. - Khan, Humaira; Cescutti-Butler, Luisa (British Journal of Midwifery, 2021)
Background In the UK, simulation in midwifery education mostly relates to developing clinical skills such as managing obstetric emergencies. However, there is minimal use of neonate simulators in educating student midwives on the impact of teratogens on fetal development. There is also limited research on using neonatal simulators as a creative pedagogical tool in undergraduate midwifery education. Objectives The two main objectives of this study were to ascertain whether students could recognise the physical impact of teratogens in the early postnatal period while interacting with simulators and to explore whether midwifery students understood their role as future midwives when working with pregnant women who may be misusing substances. Methods This qualitative research involved Level 4 student midwives from south England. A taught session on protecting the unborn environment was provided and students were tasked to interact with low fidelity fetal alcohol syndrome simulators and medium fidelity drug affected simulators. Student responses to group activities, such as interacting with the simulators and considering their role as future midwives in educating pregnant women about the impact of teratogens on a fetus and newborn baby, were collected. Results The use of the simulators was a useful pedagogical tool for enhancing student knowledge around teratogenesis and fetal impact. Conclusions Neonatal simulators can be used to engage undergraduate midwifery students and enhance their learning and knowledge.